Penerapan Nilai Syariah dalam Jabatan Notaris di Lombok Nusa Tenggara Barat - Maulidi, Mohammad Jeffry; Mutawali; Yakin, Nurul (Religion, Culture, and State Journal, 2021)
The notary is public officials who are authorized to make authentic deeds regarding all actions and agreements based on the constitution of the notary position. This study examines the correlation between Islamic education and the position of a notary. In particular, this study aims to understand the nature of the principles of sharia values ​​in the notary position, the implementation of the notary in making sharia deeds, and the ideal construction of sharia-based notary positions. This research is field research using qualitative methods. In terms of data collection, I applied some techniques such as observation, interviews, and documentation. The main data source in this research is the notarial study program at the University of Mataram. So, to get a good source, I conduct observations and collect accurate data by visiting the Main Office of the NTB Syariah Bank and the Notary Office on the island of Lombok. The study results show that the higher the Islamic thinking and methods used in teaching following competency standards and fresh ijtihad, the higher the quality of education in the unique skills of prospective notaries. Another finding is that the notary person is required to have strong moral that obey the prophet way in recording transactions (writing) in non-cash muamalah activities for a specified time, which is currently better known as Islamic institutional financing to determine whether it is legal (authentic deed) and not legal (underhand deed) deed made because it is classified as a correct item and does not conflict with iltizam, which is under sharia transaction principles and leaves conventional transactions. This study also proves that the current growth of sharia transactions and technology creates a positive correlation, namely the increasing religious value of Muslim Notaries in Lombok.